ANALISIS PENGUKURAN KINERJA BANK PENDEKATAN BALANCED SCORECARD - Ema Nur Herlindayantri (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims to measure the performance of PT. Bank XY according to fourpersepectives of balanced scorecard, consisiting of: financial perspective, customerperspective, internal business perspective and learning & growth perspective. Thisresearch used balanced scorecard as the performance measurement because balancedscorecard is able to measure organizational performance both from financial andnon-financial aspects. This research was conducted by collecting primary and secondarydata. Comparative analysis used in this research to evaluate PT. Bank XY performancebetween periods. The performance measurement results show that the overallperformance of PT. Bank XY is good enough seen from four perspectives of balancedscorecard. The learning and growth perspective analysis shows a good result. Thefinancial and customer analysis show adequacy results. Meanwhile, PT. Bank XY isconsidered as performing inadequacy in internal business process perspective and needssome improvement in some aspects, especially in market share, AETR, and after-salesservice.Keywords: Performance, Balanced Scorecard, Financial Perspective, CustomerPerspective, Internal Business Process Perspective, Learning and Growth Perspective.